Program Pengentasan Kemiskinan Berbasis Potensi Lokal di Kabupaten Bojonegoro - Ahmad Sholikin (Badan Koordinasi Kegiatan Kesejahteraan Sosial, 2024)
Poverty alleviation is one of the main challenges faced by many local governments, including Bojonegoro Regency. Bojonegoro has rich local potential, especially in the agriculture, livestock, and natural resources sectors such as oil and gas. This study aims to analyze poverty alleviation programs based on optimizing local potential in Bojonegoro. Through a descriptive qualitative approach, data was collected from various sources, including policy documents, interviews with local stakeholders, and field observations. The results show that community-based economic development by utilizing local resources has a significant impact in reducing poverty. However, there are still a number of challenges, such as low access to capital, education, and technology that limit the community's ability to optimize existing potential. The main recommendation of this study is the need for synergy between the government, private sector, and communities in creating more inclusive and sustainable programs, with a focus on increasing local capacity and access to markets. Thus, poverty alleviation in Bojonegoro can be more effective and equitable, in line with the vision of sustainable regional development.